2009
DOI: 10.1103/physrevd.80.099901
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Axial nucleon and nucleon toΔform factors and the Goldberger-Treiman relations from lattice QCD [Phys. Rev. D76, 094511 (2007)]

Abstract: We evaluate the nucleon axial form factor, GA(q 2 ), and induced pseudoscalar form factor, Gp(q 2 ), as well as the pion-nucleon form factor, GπNN (q 2 ), in lattice QCD. We also evaluate the corresponding nucleon to ∆ transition form factors, C A 5 (q 2 ) and C A 6 (q 2 ), and the pion-nucleon-∆ form factor GπN∆(q 2 ). The nucleon form factors are evaluated in the quenched theory and with two degenerate flavors of dynamical Wilson fermions. The nucleon to ∆ form factors, besides Wilson fermions, are evaluated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
86
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 20 publications
14
86
1
Order By: Relevance
“…This point was explicitly illustrated by using the Skyrme soliton model form factors [30]. In fact, this conclusion is coherent with the early hard core regularizations [3,4,5], recent lattice calculations [36] (where an extremely hard Λ πN N ∼ 1.7GeV and a rather flat behaviour are found) and, as we will show, with the renormalization approach we advocate.…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…This point was explicitly illustrated by using the Skyrme soliton model form factors [30]. In fact, this conclusion is coherent with the early hard core regularizations [3,4,5], recent lattice calculations [36] (where an extremely hard Λ πN N ∼ 1.7GeV and a rather flat behaviour are found) and, as we will show, with the renormalization approach we advocate.…”
Section: Introductionsupporting
confidence: 61%
“…These include meson theory [22,23,24,25,26,27], Regge models [28], chiral soliton models [29,30,31,32], QCD sum rules [33] the Goldberger-Treimann discrepancy [34] or lattice QCD [35,36] and quark models [37]. Most calculations yield rather small values Λ πN N ∼ 800MeV generating the soft form factor puzzle for the OBE potential for several years since the cut-off could not be lowered below Λ πN N = 1.3GeV without destroying the quality of the fits and the description of the deuteron [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the discrepancy in the momentum dependence of the dominant dipole form factor remained with lattice results having smaller values at low q 2 -values and a weaker dependence on q 2 . Using the same set of sequential propogators as in the electromagnetic case the axial and pseudo-scalar N to ∆ form factors were studied [21,30]. The strong coupling constant g πN ∆ and non-diagonal Goldberger-Treiman relation were examined in detail and it was demonstrated that the behaviour is very similar manner to the corresponding relations in the nucleon system.…”
Section: Introductionmentioning
confidence: 99%
“…MeV [21,[28][29][30]. This calculation showed that the unquenched results on the Coulomb quadrupole form factor at low q 2 decreased towards the experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation